2021
DOI: 10.1177/14648849211036301
|View full text |Cite
|
Sign up to set email alerts
|

Journalism ethics with Foucault: Casually employed journalists’ constructions of professional integrity

Abstract: This article examines how journalists in non-permanent employment respond to their growing precarity. It is based on in-depth interviews with freelance journalists and interns who find that their working lives increasingly require entrepreneurial efforts. To work towards continuous access to journalistic work, these casually employed journalists engage in self-management and self-branding. To be able to make a living, they subsidize their income with work for clients outside of journalism that frequently offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
4
0
1
Order By: Relevance
“…The only addition for the second set of interviews in 2021 were questions about developments in the journalists' careers since the first interview, including the impact of the pandemic. Publications from the first set of interviews with freelance journalists focused mainly on their perceptions of working conditions (Gollmitzer, 2022(Gollmitzer, , 2023. In contrast, the current study was motivated by an interest in freelancers, non-work activities and social relations outside of work proper before and during the pandemic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only addition for the second set of interviews in 2021 were questions about developments in the journalists' careers since the first interview, including the impact of the pandemic. Publications from the first set of interviews with freelance journalists focused mainly on their perceptions of working conditions (Gollmitzer, 2022(Gollmitzer, , 2023. In contrast, the current study was motivated by an interest in freelancers, non-work activities and social relations outside of work proper before and during the pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…The past ten years have seen a flourishing of scholarship documenting the increasingly precarious working conditions and incomes of contemporary journalists (Cohen, 2016; Edstrom & Ladendorf, 2012; Gollmitzer, 2023). This includes attention to strategies for fighting precarity, from individualized responses such as exodus from the profession (Örnebring & Möller, 2018) or work refusal (Norbäck, 2021) to collective initiatives such as the current unionization wave of workers in the digital media industries (de Peuter & Cohen, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In their research in Ireland, Hayes and Silke (2018) found that new entrants to freelance journalism were struggling to get paid for their work and were forced to work for free at times, which many did in the hope that it may translate to paid work. Rick and Hanitzsch (2023) concluded that freelance Journalists in particular faced increasing uncertainty due to the pandemic, while Gollmitzer (2023Gollmitzer ( , p. 1024 argued that the growing precarity facing freelance journalists was such that many have to subsidize their income with other workwhich they referred to as "money jobs"-where pay is higher. Realistically that is not sustainable in the long term and will ultimately lead to graduates opting for opportunities elsewhere where there is more stability and better pay and conditions.…”
Section: Precarious Working Conditionsmentioning
confidence: 99%
“…The economic instability in the media industry has led to greater precarity in the job market, employment insecurity and a growing number of freelancers and casually employed journalists (Gollmitzers, 2021;Mathisen, 2018). Ethical challenges arise as the affiliation between journalism and advertising deepens, both as a consequence of the changing professional roles of news producers these developments bring about and in terms of ensuring continued journalistic autonomy, credibility and translparency.…”
Section: Ii) Casually Employed Journalists and Advertisingmentioning
confidence: 99%